Modelling business continuity and records management in digital environment - Kamarudin, Hanis Diyana; Hariro Samsudin, Ahmad Zam; Jamaluddin, Aniza (Research and Innovation Division, Universiti Teknologi MARA (UiTM) Selangor, 2025)
Small and medium-sized enterprises (SMEs) play a pivotal role in national economies, employing nearly two- thirds of the labour force and contributing significantly to government income. Selangor, a thriving economic landscape with the highest number of establishments among Malaysian states, relies predominantly on SMEs. The strategic location of Selangor at the heart of Peninsular Malaysia has attracted numerous SMEs, making it crucial to understand and enhance their business continuity and records management practices. To address this, a qualitative multiple case study was conducted, focusing on SMEs in Selangor. The study aimed to evaluate the comprehensiveness of business continuity management, assess business continuity plans (BCPs) for records management, and explore the implications of non-compliance with BCPs for SMEs. The research utilized document reviews and interviews with SME business owners and continuity managers, explicitly focusing on managerial-level respondents in the records and information system department. Findings underscored the importance of identifying vital records within SMEs, such as active contracts, financial records, and personal customer information. Regular updates to BCPs were highlighted as crucial to align with organizational changes. The study revealed diverse approaches to records management, with some SMEs designating division managers as custodians and others involving management, records committees, and imaging specialists. Integrating stakeholder perspectives was identified as a critical factor in developing comprehensive BCPs. Discrepancies were observed in including records in BCPs, emphasizing the need for a standardized understanding. An organized BCP was deemed essential, with SMEs emphasizing the significance of recovery plans, regular audits, and discussions with top management. In conclusion, the research findings emphasize the need for SMEs in Selangor to evaluate and integrate their BCPs and records management practices to enhance overall resilience. The study contributes practical insights for improving business continuity and records management efforts, providing valuable guidance on identifying vital records, engaging stakeholders, specifying roles, and maintaining organized BCPs. The results offer SMEs in Selangor an opportunity to strengthen their readiness and resilience for business continuity by customizing strategies effectively.